2017
DOI: 10.1002/adma.201605652
|View full text |Cite
|
Sign up to set email alerts
|

High Power Density Electrochemical Thermocells for Inexpensively Harvesting Low‐Grade Thermal Energy

Abstract: Continuously operating thermo-electrochemical cells (thermocells) are of interest for harvesting low-grade waste thermal energy because of their potentially low cost compared with conventional thermoelectrics. Pt-free thermocells devised here provide an output power of 12 W m for an interelectrode temperature difference (ΔT) of 81 °C, which is sixfold higher power than previously reported for planar thermocells operating at ambient pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(219 citation statements)
references
References 26 publications
(43 reference statements)
5
214
0
Order By: Relevance
“…226,227 There are also additional electrochemical harvesting mechanisms to couple with the harvesting approaches described here. For example, there are sensitised thermal cells, thermo-galvanic and thermo-electro-chemical cells (thermocells), [228][229][230][231][232][233][234][235] where the dependence of electrode potential on temperature is used to construct harvesting thermal cycles and this has recently been reviewed. 236 Piezo-galvanic effects have even been observed where applying an asymmetric force to an electrolyte cell produces an electrical response 237 and thermo-magnetic effects for water splitting.…”
Section: Discussionmentioning
confidence: 99%
“…226,227 There are also additional electrochemical harvesting mechanisms to couple with the harvesting approaches described here. For example, there are sensitised thermal cells, thermo-galvanic and thermo-electro-chemical cells (thermocells), [228][229][230][231][232][233][234][235] where the dependence of electrode potential on temperature is used to construct harvesting thermal cycles and this has recently been reviewed. 236 Piezo-galvanic effects have even been observed where applying an asymmetric force to an electrolyte cell produces an electrical response 237 and thermo-magnetic effects for water splitting.…”
Section: Discussionmentioning
confidence: 99%
“…→ Fe(CN) 6 3− + e − ) at the hot anode, which is heated due to its contact with the back of the solar cell panel, and the electrons are transferred to the electrode. The electrons produce electrical power through an external load and are transferred to the cold cathode by the potential difference between the electrodes at both ends [36]. In the cathode, which is at a relatively low temperature, a reduction reaction of Fe(CN) 6 3− and the electrons occurs (i.e., Fe(CN) 6 3− + e − → Fe(CN) 6 4− ), closing the circuit loop and maintaining the electrical neutrality of the electrolyte.…”
Section: mentioning
confidence: 99%
“…Molecules 2020, 25, x FOR PEER REVIEW 3 of 10 the electrodes at both ends [36]. In the cathode, which is at a relatively low temperature, a reduction reaction of Fe(CN)6 3− and the electrons occurs (i.e., Fe(CN)6 3− + e − → Fe(CN)6 4− ), closing the circuit loop and maintaining the electrical neutrality of the electrolyte.…”
Section: mentioning
confidence: 99%
“…Recent studies have shown that carbon-based materials are a promising electrode material for TGCs (7). A power generation of 12 W/m 2 using activated carbon cloth as an electrode material (8).…”
Section: Motivation and Research Backgroundmentioning
confidence: 99%
“…Fuel cells (126), dye sensitize solar cells, thermogalvanic cells (1,8,127), redox flow cells (128,129) are examples for energy generation/conversion electrochemical devices. Supercapacitors (130,131), pseudo capacitors (132), batteries (133)(134)(135) are examples of energy storage electrochemical devices.…”
Section: Electrochemical Cellmentioning
confidence: 99%